Pengaruh Kualitas Pelayanan Administrasi Akademik Terhadap Kepuasan Mahasiswa Politeknik Negeri Bandung - Setiawardani, Maya (Jurnal Riset Bisnis dan Investasi, 2018)
Service is an effort made to the customer to meet customer expectations. While the quality of service as an effort to meet the needs and desires of consumers and the accuracy of delivery in counterbalance consumer expectations. Bandung State Polytechnic is a vocational education institution that prepares its graduates ready to work. In achieving these objectives, it should be supported by the service of academic administration of quality to the needs and desires of students fulfilled. This study aims to illustrate how the quality of academic services according to student perceptions, describes the level of satisfaction of students, and whether there is a positive and significant influence between the quality of academic administration services there is student satisfaction. The results of this study found that the overall quality of academic administration services have been good, and student satisfaction is also good. The quality of academic administration services has a positive and significant impact on student satisfaction. Nevertheless, the quality of service still needs to be improved again such as hospitality and discipline officers, the availability of flow/chart of each service and availability of LCD projector. In addition, the overall quality of service needs to be improved again into excellent service.